Mentoring with ebooklet on duration of exclusive breasfeeding - Hapsari; Indah Juliana Madjid (Journal of diversity in learning (JDIL), 2022)
In Indonesia, Infant Mortality Rate (IMR are highest in 2013). One of prevention efforts to reduce infant mortality rate is Exclusive Breastfeeding. Lack of Exclusive Breastfeeding is one of the problems in Indonesia. Malang has nutrition problem of Complementary feeding practice before six month old. Nutrition education about Exclusive Breastfeeding should be carried out to support Exclusive Breastfeeding practice. E-booklet is modification from booklet with a easily language punctuated by images and has visual messages in cellular mobile phone expected to increase Exclusive Breastfeeding practice. This study aims to Analyze the Effects of Mentoring on Duration of Exclusive Breastfeeding Implementation. This research design uses Quasi Experiment with Posttest Only Control Group Design. This research was conducted in the working area of Puskesmas Kepanjen Malang Regency. The number of samples of this study were 42 pregnant women who would give birth in April - June 2017, divided in to control and treatment groups. Mann-Whitney statistical results showed that there was difference in duration of Exclusive Breastfeeding (p=0,000) in the control and treatment group. The conclusion of this research is that Mentoring with E-Booklet gives positive effect to duration of Exclusive Breastfeeding.